The Efficacy of E-governance in Promoting Community Participation - Tshikovhi, Lufuno (My University, 2026)
This study examines the efficacy of e-governance in promoting community participation within Thulamela Local Municipality (TLM). As information and communication technology (ICT) becomes increasingly integrated into public administration, e-governance has emerged as a crucial tool for enhancing transparency, accountability, and civic participation. Municipalities are increasingly utilising online platforms to better engage with their communities. To evaluate the efficacy of e-governance portals, including social media, municipal websites, and mobile applications, this study employed a mixed-methods approach. This approach combined quantitative surveys with qualitative interviews involving community members and municipal officials. The choice of mixed methods was made to gain a deeper understanding of the research problem. The study has five main objectives. To accomplish these objectives, the researcher adopted a pragmatism paradigm and utilised descriptive and contextual design. Nonprobability sampling methods, specifically purposive sampling, were employed to select participants. In total, 130 individuals were sampled, including 10 municipal officials who participated in interviews and 120 who completed structured questionnaires. Data collection was conducted through two main methods: structured questionnaires and interview schedules. For data analysis, the quantitative data obtained from questionnaires were analysed using statistical methods with the Statistical Package for Social Sciences (SPSS), Version 30.0. The results were presented in the form of tables, frequencies, and percentages. Qualitative data from the interviews were analysed using NVivo Version 15.0, employing thematic analysis to group the data into themes and present the findings in a narrative format. The study explored how e- governance facilitates community participation, the challenges faced during its implementation, and the municipality's responsiveness to digital feedback. The findings of this study revealed that e-governance has significantly enhanced accessibility and convenience for community participation in Thulamela Local Municipality. The study emphasised the need for improved municipal strategies to incorporate digital feedback into decision-making processes. This research contributes to the evolving field of e-governance and participatory democracy. It offers recommendations to enhance e-governance in local governance and provides valuable insights to policymakers, municipal officials, and community stakeholders on effectively leveraging technology for more inclusive decision-making in TLM. The major findings in this study are: ➢ There are relationships between e-governance and community participation in TLM. ➢ The current e-governance of TLM is ineffective in promoting community participation due to poor network services in rural areas, high data costs, budget constraints, and delays in updating information. ➢ Thulamela Local Municipality still faces several challenges in implementing e- governance to promote community participation, including limited internet access, a lack of digital literacy, language barriers, inadequate training and awareness, high data costs, Trust issues, ideological barriers, and financial and infrastructural challenges. ➢ TLM has several initiatives to strengthen community participation through e- governance, including digital literacy workshops and training sessions, as well as social media platforms, to encourage residents to engage with e- governance. ➢ A dedicated help desk, training sessions for both municipal officials and residents, and expanded internet connectivity enhance participation through e- governance portals. The following are the recommendations based on the study findings ➢ The Thulamela Local Municipality should support community members by providing an opportunity to express their voices through e-governance portals, allowing them to prioritise their needs. ➢ Simplifying e-governance processes further and providing user training or support mechanisms to enhance effectiveness. ➢ Implement multilingual platforms, simplify content, and provide educational support programs to promote inclusivity and equitable participation in digital initiatives. ➢ The municipality’s annual community participation plan should be implemented to ensure continuous learning and participation. TLM should invest in broadband infrastructure, establish public Wi-Fi hotspots, and collaborate with network providers to enhance participation through e- governance.
M. Admin.
Department of Public and Development Administration
Keywords: Community participation; UCTD; Digital Platforms; Efficacy; E-Governance